Bercermin pada Penanggalan Masehi - Rusdin Muhalling (Institut Agama Islam Negeri (IAIN) Kendari, 2008)
So far the system of determining the beginning of the month of Qamariyah for Muslims, has not been able to satisfy because there are still differences of perception in determining the beginning and the end of Ramadan and Dhul-Hijjah. Because of this problem,